2003
DOI: 10.1002/elps.200305491
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical and biomedical applications of chiral capillary electrophoresis and capillary electrochromatography: An update

Abstract: Pharmaceutical and biomedical applications of chiral capillary electrophoresis and capillary electrochromatography: An updateCapillary electrophoresis is often considered an ideal method for the chiral analysis of compounds due to the high separation power of the technique and has therefore found widespread acceptance for the analysis of drugs and pharmaceuticals. In contrast, capillary electrochromatography is still more or less in an infancy state searching for its place among the analytical separation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 151 publications
0
58
0
Order By: Relevance
“…Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Since chiral resolution was first described in CE by Zare and co-workers, 1,2 many CE enantioseparation methods have been reported, as previously reviewed. [3][4][5][6][7][8][9][10] These methods are based on several resolution mechanisms, such as ligand-exchange, inclusioncomplexation, ion-pair interactions, micellar electrokinetic chromatography (MEKC) and microemulsion electrokinetic chromatography (MEEKC). MEEKC has several optimization advantages over other techniques in terms of selectivity, 11 elution range and composition.…”
Section: Introductionmentioning
confidence: 99%
“…99%. The structure of intermediate (3) was confirmed by high-resolution MALDI-TOF-MS [12] using a Voyager Elite XL mass spectrometer equipped with delayed extraction capability (Perceptive Biosystems, Framingham, MA, USA), and 1 H NMR, 13 C NMR, double-quantum filtered 1 H-1 H correlation spectroscopy (COSY) and 1 H- 13 C heteronuclear correlation spectroscopy (HETCOR) using Varian UnityPlus spectrometers (300 MHz and 500 MHz, both from Varian, Walnut Creek, CA, USA). Hexakis(2,3-di-O-methyl-6-dimethyl-t-butylsilyl)-a-CD was then converted into intermediate (4), hexakis(2,3-di-O-methyl)-a-CD, by removing the dimethyl-t-butylsilyl protecting group with hydrogen fluoride (HF) in ethanol.…”
Section: Synthesis Of the Sodium Salt Of Hxdmsmentioning
confidence: 99%
“…CE enantiomer separations were last reviewed in the annual enantiomer separations issue of Electrophoresis [1]. That review pointed out that sulfated cyclodextrins [2], including the single-isomer, regioselectively substituted 6-O-sulfo CDs [3][4][5][6][7][8][9][10] were the most widely used resolving agents for the separation of the enantiomers of pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%